Diagnóstico de fuentes de contaminación con metales pesados y microbiológicos del queso fresco no pasteurizado en Canuto – Chone – Manabí - Loor Cedeño, Josué Sebastián (2024)
The purpose of the research was to identify the sources of contamination with heavy metals and microorganisms in unpasteurized fresh cheese in the parish of Canuto, canton Chone, province of Manabí. For this purpose, a methodology based on an interview, questionnaire and check list was designed, which allowed the collection of information from each of the farms that produced fresh cheese with pasteurized milk. A Pearson correlation was applied in the SPSS statistical program to determine the influence of factors such as sanitation and biosafety, raw material handling and production factors, packaging and quality assurance. The microbiological quality of samples collected from each of the farms was also evaluated. The situational diagnosis identified that sanitation and biosafety are two of the main aspects that are considered sources of heavy metal and microbiological contamination. The results obtained from the analyses showed lead levels <0.001, except for one of the samples that showed levels of 0.09, while cadmium and mercury values were <0.05. Microbiological analyses showed that three of the four farms presented unacceptable levels of Enterobacteriaceae, Escherichia coli, Staphylococcus aureus, while for Salmonella and Listeria, three of the four farms presented absence. The implementation of detailed manuals with procedures was proposed.